Neglecting physician desires to teach at an academic medical facility: A mixed method investigation of the consequences. (2nd September 2022) - Klinefelter, Zachary; Heavner, Smith; Kennedy, Ann Blair; Britt, Thomas; Taylor, Shannon Stark; Benedum, Molly
Abstract: Purpose: Recent findings have suggested that physicians who spend more time participating in their most meaningful job activities (e.g. teaching) are less likely to experience burnout. The current study aimed to expound upon this finding, focusing specifically on the role of teaching in promoting meaning and preventing burnout. Method: A total of 428 physicians at a large academic healthcare institution completed an online survey that included measures of burnout and other relevant variables. In the second part of this study, 20 physicians participated in interviews with the aim of expounding upon and contextualizing the findings from Part 1. Results: Results from Part 1 suggested that although meaningfulness derived from teaching was associated with reduced burnout, this association was only true for those who indicated that clinical teaching was among the most meaningful parts of being a physician. In addition, physicians were less likely to spend time working on their most meaningful job activity when it was teaching. Part 2 illustrated why teaching in the clinical environment can be so meaningful and protective against burnout. Conclusions: Many physicians are unable to teach due to the increasing demands of medical institutions, which may contribute to the increasing levels of burnout in healthcare providers.